2008
DOI: 10.1080/00016480701719011
|View full text |Cite
|
Sign up to set email alerts
|

Audiological and genetic features of themtDNA mutations

Abstract: Conclusions Significant difference in the incidence of mitochondrial DNA (mtDNA) mutations was found between the Chinese and USA populations. The identification of the mtDNA A1555G mutation in a large proportion of Chinese probands with nonsyndromic sensorineural hearing loss (NSHL) provides a molecular explanation for the high prevalence of aminoglycoside-induced deafness in China. Objective The aim was to characterize the audiological and genetic features of NSHL due to mutations in mtDNA. Subjects and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…For example, previous findings showed that the frequency was 2.9% in patients with NSHL [14]. Guo et al [3] reported that the frequency was 8.75% in NSHL patients in special education schools in northwest China, and 15.5% was reported by Liu et al [6], even up to 40% in 10 Taiwan families with deafness [17]. Noguchi et al [16] reported that the mutation frequency was higher in familial patients than in sporadic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous findings showed that the frequency was 2.9% in patients with NSHL [14]. Guo et al [3] reported that the frequency was 8.75% in NSHL patients in special education schools in northwest China, and 15.5% was reported by Liu et al [6], even up to 40% in 10 Taiwan families with deafness [17]. Noguchi et al [16] reported that the mutation frequency was higher in familial patients than in sporadic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The differences were mainly found in mutation frequencies, including disease-causing mutation frequency (homozygous or compound heterozygous mutation), and risk allele carrying frequency (homozygous, compound heterozygous and heterozygous mutation). For example, the reported m.A1555G mutation frequency in Chinese NSHL patients varied from 1.67% to 15.5% in several independent studies [5,6]. The difference among reported mutation frequencies of GJB2 gene was very large.…”
Section: Introductionmentioning
confidence: 99%
“…111 Our data shows that 88% of severe-profound mt DNA deafness carrying the homoplasmic A1555G mutation had exposure to aminoglycosides. 112 …”
Section: Introductionmentioning
confidence: 99%
“…Our recent study shows that the mt DNA A1555G is responsible for deafness for a large proportion of NSHL, accounting for 15.5% of SNHL cases from the special clinics for deaf in China. 112 …”
Section: Introductionmentioning
confidence: 99%
“…Homoplasmic m.1555A > G and m.1494C > T, located at the highly conserved decoding site of the 12S ribosomal RNA gene, have been identified as a cause of maternally inherited non-syndromic HL. HL inherited through the mitochondria accounts for less than 1% of all HL, though the frequency of m.1555A > G in Chinese non-syndromic HL patients can vary from 1.67%-15.5% [1720]. In this study, 5 cases (0.72%,5/695) were found to carry homoplasmic m.1555A > G, out of which, 1 had a history of aminoglycoside antibiotic usage and another had a recognizable audio-profile of aminoglycoside-induced HL.…”
Section: Discussionmentioning
confidence: 99%